2012
DOI: 10.1007/s11250-012-0213-2
|View full text |Cite
|
Sign up to set email alerts
|

Free range and deep litter poultry production systems: effect on performance, carcass yield and meat composition of cockerel chickens

Abstract: This study was carried out on 150 cockerel chickens each of Harco Black and Novogen strains to determine their performance, carcass yield and meat composition on free range and deep litter production systems. The birds were brooded for 4 weeks and thereafter allotted to the different production systems for a period of 12 weeks. Each production system was allotted 150 chicks (75 chicks per strain) with three replicates of 25 chicks. The birds on deep litter production system were fed ad libitum while each bird … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…Although free range was available to slow-growing strains, their growth rate was not comparable with Cobb-500. Similar findings were reported in a study in which intensively reared Harco black genotype had higher morphological lengths of tibia than free-range Novogen strains (Sogunle et al, 2012). Contrary to the current findings, Akşit et al (2017) reported no effect of environmental enrichment on tibia length.…”
Section: Resultssupporting
confidence: 82%
“…Although free range was available to slow-growing strains, their growth rate was not comparable with Cobb-500. Similar findings were reported in a study in which intensively reared Harco black genotype had higher morphological lengths of tibia than free-range Novogen strains (Sogunle et al, 2012). Contrary to the current findings, Akşit et al (2017) reported no effect of environmental enrichment on tibia length.…”
Section: Resultssupporting
confidence: 82%
“…Higher meat bone ratio in broilrs might be due to more proportionate growth of muscles than bones. The present results are in congruent with Sogunle et al, (2013) [14] in Vanaraja chicken.…”
Section: Carcass Characteristicssupporting
confidence: 94%
“…The variation in the amount of certain tissue will influence the proportion of other tissues and, in situations of similar weight, birds with a higher amount of muscle tissue will indicate individuals with a higher potential for growth and meat production (SOGUNLE et al, 2013). This was also observed for females that presented a higher proportion of meat and a lower proportion of bone in the legs (Table 3).…”
Section: Resultsmentioning
confidence: 89%